Dynamics of Civil Structures, Volume 2 Proceedings of the 39th IMAC, A Conference and Exposition on Structural Dynamics 2021 - Grimmelsman, Kirk.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Dynamics of Civil Structures, Volume 2: Proceedings of the 39th IMAC, A Conference and Exposition on Structural Dynamics, 2021, the second volume of nine from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of the Dynamics of Civil Structures, including papers on: Structural Vibration Humans & Structures Innovative Measurement for Structural Applications Smart Structures and Automation Modal Identification of Structural Systems Bridges and Novel Vibration Analysis Sensors and Control .
Chapter 1. Particle Filters and Auto-Encoders Combination for Damage Diagnosis on Hysteretic Non-Linear Structures Subject to Changing Environmental Conditions -- Chapter 2. A New Benchmark Problem for Structural Damage Detection: Bolt Loosening Tests on a Large-Scale Laboratory Structure -- Chapter 3. Implementation of an Organic Database Structure for Population-based Structural Health Monitoring -- Chapter 4. Estimation of Wind Turbine Blade Forces Using Strain Measurements Collected at Blade Roots -- Chapter 5. On Health-State Transition Models for Risk-Based Structural Health Monitoring -- Chapter 6. Cointegration for Structural Damage Detection Under Environmental Variabilities: An Experimental Study -- Chapter 7. Footbridge Vibrations and Modelling of Pedestrian Loads -- Chapter 8. Multi LSTM Based Framework for Ambient Intelligence -- Chapter 9. Operational Modal Analysis and Finite Element Model Updating of a 53 Story Building -- Chapter 10. An Overview of Deep Learning Methods used in Vibration-based Damage Detection in Civil Engineering -- Chapter 11. Best Paper: Transfer Learning from Audio Domains a Valuable Tool for Structural Health Monitoring -- Chapter 12. Best Paper: Experimental Evaluation of Drive-by Health Monitoring on a Short Span Bridge Using OMA Techniques -- Chapter 13. Investigation of Low-Cost Accelerometer Performance for Vibration Analysis of Bridges -- Chapter 14. Real-time Human Cognition of Nearby Vibrations Using Augmented Reality -- Chapter 15. Understanding Errors from Multi-Input-Multi-Output (MIMO) Testing of a Cantilever Beam -- Chapter 16. Load-Displacement Behavior Clustering of RC Shear walls using Functional Data Analysis.
Keywords: Buildings -- Design and construction; Statics; Light construction; Steel construction; Lightweight construction; Building materials; Civil engineering; Building Construction and Design; Mechanical Statics and Structures; Light-weight Construction, Steel and Timber Construction; Building Materials; Civil Engineering; Civil engineering -- Congresses; Structural dynamics -- Congresses